A Purified, Solvent‐Intercalated Precursor Complex for Wide‐Process‐Window Fabrication of Efficient Perovskite Solar Cells and Modules. Issue 28 (27th May 2019) - Ozaki, Masashi; Shimazaki, Ai; Jung, Mina; Nakaike, Yumi; Maruyama, Naoki; Yakumaru, Shinya; Rafieh, Alwani Imanah; Sasamori, Takahiro; Tokitoh, Norihiro; Ekanayake, Piyasiri; Murata, Yasujiro; Murdey, Richard; et al.
Abstract: A high‐purity methylammonium lead iodide complex with intercalated dimethylformamide (DMF) molecules, CH3 NH3 PbI3 ⋅DMF, is introduced as an effective precursor material for fabricating high‐quality solution‐processed perovskite layers. Spin‐coated films of the solvent‐intercalated complex dissolved in pure dimethyl sulfoxide (DMSO) yielded thick, dense perovskite layers after thermal annealing. The low volatility of the pure DMSO solvent extended the allowable time for low‐speed spin programs and considerably relaxed the precision needed for the antisolvent addition step. An optimized, reliable fabrication method was devised to take advantage of this extended process window and resulted in highly consistent performance of perovskite solar cell devices, with up to 19.8 % power‐conversion efficiency (PCE). The optimized method was also used to fabricate a 22.0 cm 2, eight‐cell module with 14.2 % PCE (active area) and 8.64 V output (1.08 V/cell). Abstract : No rush : High‐efficiency CH3 NH3 PbI3 perovskite solar cells (19.8 % power‐conversion efficiency, PCE) and large‐area eight‐cell modules (14.2 % PCE, 8.64 V) were readily fabricated from a purified perovskite precursor material, CH3 NH3 PbI3 ⋅DMF (see picture). The low volatility of the pure DMSO solvent (as compared to DMF/DMSO) extended the allowable time for low‐speed spin programs and relaxed the precision needed for the antisolvent addition step.